Analisis Pengaruh Intellectual Capital terhadap Keputusan Investor (Studi pada Perusahaan Asuransi yang Terdaftar di Bursa Efek Indonesia) - Arlistria Muthmainnah; Muhammad Ali; Andi Reni (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This study aims to determine the effect of intellectual capital on investor decisions in choosing shares in insurance companies listed on the Indonesia Stock Exchange (IDX). This study uses a descriptive quantitative approach using insurance companies on the Stock Exchange in the 2013-2017 period as a population. The sampling method used purposive sampling, so that there are 10 companies that meet the criteria as a sample. Intellectual capital variables are measured using the Value Edded Intellectual Coefficient (VAICTM) method, whose components consist of VACA, VAHU, and STVA. And investor decisions are measured by Price to Book Value (PBV). As for testing the hypothesis using panel data regression methods and path analysis which is processed through Microsoft Excel software and Eviews 10. The results of this study indicate that intellectual capital does not directly influence investor decisions (PBV), VACA and VAHU have Prob values <0.05, which means that VACA and VAHU have a significant effect on PBV. While STVA has a value of Prob> 0.05, it means that STVA has no significant effect on PBV. This is because in the Indonesian capital market there are still many short-term investors who make decisions based on performance and have not utilized how intellectual capital can increase the company's potential. In addition, the shares of Indonesian insurance companies are less liquid in the capital market, and there are market psychological factors that influence investors' decisions.